Agricultural Land Use Allocation under Current and Projected Scenarios - Gella Patria L. Abella; Felino Lansigan; Jerrold Tubay (International Journal of Technology, 2021)
A model-based systems approach in optimizing agricultural land use spatial allocation integrating climate change adaptation was developed in this study. A land use planning and analysis system framework was modified and adopted under current conditions and anticipated scenarios for 2035. Climatic scenarios were reflected in land suitability ratings by conducting a land evaluation. All agricultural inputs and outputs were estimated and analyzed by multiple goal linear programming using Gurobi software. The results demonstrated that under current conditions, the city can meet its crop production, increase total farmers’ net income, maximize agricultural labor, and provide a suitable residential area by optimally allocating grids to suitable uses. Under the 2035 scenario, the city can still achieve its development goals despite the change in land suitability and increase in population.